2015
DOI: 10.3961/jpmph.15.055
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Sarcopenia and Sarcopenic Obesity With Metabolic Syndrome Considering Both Muscle Mass and Muscle Strength

Abstract: Objectives:We investigated the associations of sarcopenia-defined both in terms of muscle mass and muscle strength-and sarcopenic obesity with metabolic syndrome.Methods:Secondary data pertaining to 309 subjects (85 men and 224 women) were collected from participants in exercise programs at a health center in a suburban area. Muscle mass was measured using bioelectrical impedance analysis, and muscle strength was measured via handgrip strength. Sarcopenia based on muscle mass alone was defined as a weight-adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 41 publications
(72 reference statements)
1
51
0
2
Order By: Relevance
“…Loss of muscle mass and gain of body fat with ageing may potentiate each other and maximise their effects on physical inactivity . Moreover, obesity with low muscle mass was associated with metabolic syndrome and insulin resistance; thus, obesity with low muscle mass might be predictive for mortality even in those without DM . In this study, we demonstrated obesity with low muscle mass was a predictor for dialysis mortality regardless of other anthropometric parameters in women.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Loss of muscle mass and gain of body fat with ageing may potentiate each other and maximise their effects on physical inactivity . Moreover, obesity with low muscle mass was associated with metabolic syndrome and insulin resistance; thus, obesity with low muscle mass might be predictive for mortality even in those without DM . In this study, we demonstrated obesity with low muscle mass was a predictor for dialysis mortality regardless of other anthropometric parameters in women.…”
Section: Discussionmentioning
confidence: 55%
“…Internal Medicine Journal 47 (2017) 1282-1291 © 2017 Royal Australasian College of Physicians might be predictive for mortality even in those without DM. 32,33 In this study, we demonstrated obesity with low muscle mass was a predictor for dialysis mortality regardless of other anthropometric parameters in women. Body composition parameters might provide survival information for those on maintenance dialysis.…”
Section: Sarcopenic Obesity Predicts Mortalitymentioning
confidence: 57%
See 1 more Smart Citation
“…Sarcopenia has been predictive of higher mortality in many cancers, including CRC, as was observed in our recent study. 23 Sarcopenia also has been related to higher systemic inflammatory response, 16,19,34 metabolic dysregulation, [38][39][40] and postsurgical complications, 14 and the effects of each of these muscle abnormalities appear to be independent predictors of outcomes in patients with CRC.…”
Section: Discussionmentioning
confidence: 99%
“…However, BMI cannot distinguish between fat and lean mass, which exert differing influences on metabolic dysregulation 35 and cancer survival. 36,37 In the current study, adjustment for muscularity strengthened associations.…”
Section: 34mentioning
confidence: 99%